The Impact of the Unfit Housing Program (Rutilahu) on the Quality of Life of the Community Through the Promotion of Healthy Housing in Bekasi Regency - Abdul Latip; Husnul Fitri (Publikasi Indonesia, 2026)
This study aims to analyze the impact of the Rumah Tidak Layak Huni (Rutilahu) program on the quality of life of the community through the improvement of healthy housing in Bekasi Regency. Using the World Health Organization Quality of Life–BREF (WHOQOL-BREF) approach, information was obtained on the effectiveness of housing renovations for uninhabitable houses from health, psychological, and social perspectives. This study conducted a comparative analysis between beneficiaries of the Rutilahu program and non-beneficiaries to evaluate the program’s actual impact on the community’s quality of life through improvements in healthy housing standards in Bekasi Regency. This study uses a qualitative method with a descriptive approach. Data were collected through observation, documentation, and in-depth interviews with six informants consisting of beneficiaries and non-beneficiaries of the Rutilahu program. The results of the study show that the renovation of uninhabitable houses has not made an optimal contribution to the development process and has not been effective in reducing the number of low-income residents or affecting the rate of population growth in Bekasi Regency. Analysis using the WHOQOL-BREF approach indicates that Rutilahu not only improves housing quality in terms of sanitation, ventilation, and structural safety but also has a positive impact on the quality of life of its beneficiaries.